Estimation of tensile mechanical parameters of existing masonry through the analysis of the collapse of Volterra’s urban walls (Fracture and Structural Integrity, 2019)
In this work, numerical analyses on the Volterra’s ancient walls are performed to understand the causes of a collapse occurred after an extreme rainfall (2014) and to identify the mechanical parameters that most influenced it. The stretch of collapsed wall is modelled with finite elements by distinguishing the material composing the multi-leaf wall. Non-linear static analyses are carried out with the DIANA software considering different levels of hydraulic head up to reach the collapse of the structure. The impact on the failure modes of the involved parameters, such as tensile strength, fracture energy and shear strength, are discussed. Tensile strength is found as the most relevant parameter in the failure mode. Finally, a 3-dim model is presented, and the results show a very good agreement with the failure mode actually occurred in terms of both failure modes and displacement fields. The safety evaluation is performed in the as-built and the retrofitted configuration, consisting in the wall restrained by tie-rods. The results show a significant increasing of the safety level of the retrofitted configuration showing a considerable improvement not only in terms of limit equilibrium but also in terms of structural capacity of the wall.
Keywords: Historic masonry walls; DIANA; Non-linear analysis; Vulnerability analysis; Fracture energy; Tensile strength